EFFECT OF VAGINAL SILDENAFIL ON IN VITRO FERTILIZATION SUCCESS RATES IN WOMEN WITH PREVIOUS FAILED IN VITRO FERTILIZATION ATTEMPTS - Tehraninejad, Ensieh Shahrokh; Khazei, Noushin; Ayati, Elnaz; Movafegh, Ali; Azimaraghi, Omid (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Endometrial thickness of <9 mm is a predictor of in vitro fertilization (IVF) failure, although neither pregnancy rates nor the pregnancy outcomes are dependent on the endometrial thickness alone. The impact that uterine artery blood flow has on endometrial growth is dependent on nitric oxide which concentrations could be altered by halting a cyclic guanosine monophosphate-mediated pathway with a phosphodiesterase type 5 selective inhibitor such as sildenafil. Methods: In this clinical trial, 72 patients aged below 45 years which have had at least two earlier failed IVF attempts were randomly split into two groups each consisting of 36 patients. Both groups were started on a long IVF protocol. The case group was also administered 100 mg vaginal sildenafil suppositories daily, starting on day 3 of menstruation which was continued until human chorionic gonadotropin administration. Endometrial thickness was measured using ultrasonography in both groups plus pregnancy rates were assessed in both groups. Results: The mean age of the patients in Group A who received sildenafil; in this clinical trial, 72 patients aged below 45 years which have had at least two previous failed IVF attempts were randomly split into two groups each consisting of 36 patients was 33.8±4.8 in contrast to Group B (control group) with the mean age of 33.8±4.8. Mean endometrial thickness of 8.6±0.1 mm was recorded in Group B compared to 9.0±0.7 mm in Group A (p=0.03). Of all the 36 participants who received sildenafil citrate during the IVF cycle, 12 (33.3%) patients had successful pregnancies while 24 (66.7%) failed to get pregnant. In the control group, out of the 36 participants, 10 (27.8%) patients got pregnant while 26 (72.2%) failed the cycle (p=0.9). Conclusion: This study showed that although using vaginal sildenafil during the IVF cycle does improve endometrial thickness before implantation, this does not necessarily lead to higher pregnancy rates.